Developing a customer driven supply chain strategy - Godsell, Janet (Henry Stewart Talks, 2011)
Customer driven supply chain strategy, Strategic alignment, Schema, 3S model for developing customer driven supply chain strategy, Scope, Decoupling point, Strategic inventory, Segmented supply chains, Lean, Agile, Customer value profile, Demand profile, Tailored practices, Operating model, Enablers
Reviewed at 2020/10/29